O klauzuli generalnej dobra rodziny - Sylwestrzak, Anna (Studia Prawnoustrojowe, 2019)
This publication concerns the content and meaning of the welfare of family as a constitutional value and the welfare of family as a general clause in the Family and Custody Code. The principle of the welfare of family should be included among the basic rules of family law, including its following aspects: an external aspect, being the criterion for actions taken by public authorities, and an internal aspect, which concerns the legal situation of family members, whose duties include promoting its welfare. In the course of the detailed analysis concerning the regulations given in the Family and Custody Code, it was ascertained, among other, that the directives that stem from the principle of the welfare of child and the welfare of family coincide; moreover, the scopes of both principles overlap.